PROTECTIVE EFFECT OF CASSIA FISTULA EXTRACTS AGAINST ULTRAVIOLET C INJURY IN HUMAN CORNEAL EPITHELIAL CELLS - K, DEEKSHA; ARUNACHALAM, CYNTHIA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to investigate the antioxidant activity of Indian laburnum (Cassia fistula L. [CF]) leaf extracts and their impact on ultraviolet C (UVC) radiation-induced damage on human corneal epithelial (HCE) cells. Methods: The antioxidant activity and free radical scavenging ability of CF leaf extracts were determined by in vitro methods such as 1,1-diphenyl- 2-picrylhydrazyl radical scavenging capacity, Total antioxidant capacity (TAC), and reducing power. The total phenolic content (TPC), total flavonoid content (TFC), and preliminary phytochemical screening were done to ensure the pharmacological effects of the extracts. The UVC radiation at wavelength 254 nm was used to irradiate HCE cells and cell viability was assessed by methyl thiazolyl tetrazolium assay. Results: Extracts at the concentration of 200 μg/ml did not affect the cell viability of HCE cells. Almost 50% cell death was observed after UVC irradiation at a dose of 200 J/m2. Both extracts showed a protective effect by increasing the cell viability of irradiated cells up to 57.28% and 62.39%. A dose-dependent increase in the TAC and reducing power of the extract was observed. The TPC in aqueous and ethanol extracts of CF leaves was 18.8 and 27.80 mg gallic acid equivalent/g sample while TFC was 8.47 and 16.5 mg quercetin equivalent per/gsample, respectively. Conclusions: CF leaves are a potent source of bioactive compounds with good antioxidant potential. Exposure to UVC radiation cause harmful effects on HCE cells and the extracts have shown to have potent protective effects on UV light-induced oxidative stress in HCE cells.